Electrochemotherapy for the treatment of cutaneous squamous cell carcinoma: The INSPECT experience (2008-2020) - Bertino, Giulia; Groselj, Ales; Campana, Luca G.; Kunte, Christian; Schepler, Hadrian; Gehl, Julie; Muir, Tobian; Clover, James A. P.; Quaglino, Pietro; Kis, Erika; Mascherini, Matteo; Bisase, Brian; et al. (Frontiers in Oncology, 2022)
Cutaneous squamous cell carcinoma (cSCC) is a frequent skin cancer with a high risk of recurrence characterized by tumor infiltration and poor prognosis. ECT (electrochemotherapy) is an alternative treatment option for locally advanced or recurrent cSCC that is unsuitable for surgical resection. In this study, we aimed to evaluate the data in the InspECT (International Network for Sharing Practice on ECT) registry of the referral centers and to clarify the indications for the use of ECT as a treatment modality for cSCC. Patients with primary, recurrent or locally advanced cSCC from 18 European centers were included. They underwent at least one ECT session with bleomycin between February 2008 and November 2020, which was performed following the European Standard Operating Procedures. The analysis included 162 patients (mean age of 80 years; median, 1 lesion/patient). Side effects were mainly local and mild (hyperpigmentation, 11%; ulceration, 11%; suppuration, 4%). The response to treatment per patient was 62% complete and 21% partial. In the multivariate model, intravenous drug administration and small tumor size showed a significant association with a positive outcome (objective response). One-year local progression-free survival was significantly better (p<0.001) in patients with primary tumors (80% (95% C.I. 70%-90%) than in patients with locally advanced disease (49% (95%C.I. 30%-68%). In the present study, ECT showed antitumor activity and a favorable safety profile in patients with complex cSCC for whom there was no widely accepted standard of care. Better results were obtained in primary and small tumors (<3 cm) using intravenous bleomycin administration.